The genesis of the Black-Scholes option pricing formula - Thomas Heimer; Sebastian Arend (Frankfurt School of Finance & Management, 2008)
Innovations in the finance industry are an important tool to enhance profitability and to increase a nation's wealth. It, therefore, is not astonishing that there is much empirical work on innovations in finance. Most of the work however is concerned with the design of innovative products. The question on how innovations are established and pushed through in financial markets is mostly neglected. Hardly any asks: How do we develop new ways of pricing derivatives, how do we enhance risk control, how do we generate new processes that may enhance the profitability of finance business? The second sector innovation theory in the last decades has taken a different approach. To understand innovation better researchers have focused on the question on how innovations have been emerging. Studies on the history of innovations opened a promising line of research that helps to understand innovation processes much better (see Hughes 1983 und Callon 1986). A similar approach has yet not been adapted to innovation theories in financial markets.1 Accordingly it is the articles objective to evaluate the outcome of a transfer of innovation theories from the second into the third sector. The transfer is conducted on the example of the BlackScholes option pricing formula, an innovation with a strong influence on the efficiency of decisions in the option market. The article shows how the innovation emerged and what factors influenced the diffusion process.
urn:nbn:de:101:1-2008100601
Keywords: O31; O33; P45; 330; Innovation; finance; diffusion